The Effectiveness of GABA Agonist in Decreasing Expression of NR2B Subunit of N-Methyl-D-Aspartate (NMDA) Receptor in Neuropathic Mice by Partial Sciatic Nerve Ligation (PSNL) Method - FIFTEEN APRILA FAJRIN; JUNAIDI KHOTIB; IMAM SUSILO (JURNAL ILMU KEFARMASIAN INDONESIA, 2016)
Neuropathy pain is a pain that caused by nerves injury. Nowadays, treatment for neuropathic pain change to drugs that works as GABA agonist and cause reimbalance between excitatory and inhibitory neurotransmitter in central nervous system (CNS). The present study was designed to investigate the effectiveness of gabapentin and baclofen in decreasing N-Methyl-D-Aspartate (NMDA) receptor NR2B subunit activity in neuropathic pain. Fourty mice were divided into 8 groups i.e sham, negative control, gabapentin (10, 30, 100 nmol) and baclofen (1, 10, 30 nmol). Neuropathic pain was induced by ligation of sciatic nerve with Partial Sciatic Nerve Ligation (PSNL) method). Treatments were administrated intrathecally once a day for seven consecutive days, at a week after induction. On day 15th, mice were sacrified and the spinal cord were removed quickly. The expression of NMDA receptor NR2B subunit were examined with imunohistochemistry and data were analyzed by one way anova. The result from this research was gabapentin and baclofen administration significantly decrease expression of NMDA receptor NR2B subunit in mice compared to sham group. The higher the dose, the more effective to decrease the number of neuron that express NR2B. The conclusion of this research was gabapentin and baclofen treat neuropatic pain by decreased the number of NMDA receptor NR2B subunit.